Serum levels of the Parkinson's disease-linked protein Parkin are specifically elevated in COVID-19 - Nadezhda G. Gumanova; Natalya L. Bogdanova; Alexander Yu. Gorshkov (Journal of Clinical Virology Plus)
Background: Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is known to cause various unfavorable effects, including neurodegenerative disorders. The aim of the present study was to assess comparative serum protein profiles specifically associated with COVID-19. Methods: COVID-19 infection was confirmed by the detection of immunoglobulin G (IgG)-SARS antibodies against SARS-CoV-2 S1 protein receptor-binding domain in serum samples collected in 2019–2021. IgG antibodies to adenovirus (IgG-AdV) were analyzed in serum samples collected in 2016–2018 prior the onset of the COVID-19 pandemic. Comparative protein profiling was conducted in matched serum samples with positive or negative IgG-SARS-status using the Signaling Explorer Antibody Array (SET100) that included 1358 specific antibodies in two replicates. This analysis identified Parkin as a top protein discriminating between the SARS-positive and negative status. The results were validated using in-house ELISA in the serum of participants recruited in 2019- 2021. Specificity versus another viral infection was tested in the serum samples with positive or negative status of IgG-AdV antibodies. Results: High serum levels of the Parkinson's disease-linked protein Parkin were associated with SARS-positive status (P < 0.05) but were not associated with IgG-AdV-positive-status (P > 0.05). Conclusions: Specific associations of Parkin with COVID-19 contribute to identification of the signaling pathways linked to COVID-19 effects.